Pengembangan Model Pembelajaran Histoenterpreneurship Untuk Meningkatkan Softskill Kewirausahaan Mahasiswa Pendidikan Sejarah Universitas Jambi - Purnomo, Budi; Sireger, Isrina - (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Entrepreneurship is a profession that is the vision and mission of almost all universities in Indonesia. And this is a problem for the education sector., namely how to create or build an entrepreneurial spirit in the midst of a diverse society, considering the limited available jobs. Higher education is not only a job seeker or graduate but also a job creator. This research intends to develop a histoentrepreneurship learning model to improve entrepreneurship soft skills of history education students at the University of Jambi. The research subjects were 34 students. Data collection methods with interviews and questionnaires. The development model uses Borg & Gall which was refined by Sukmadinata. The study's findings revealed that the two expert validators' assessment received a score of 4.2 (very good), the small group test received a score of 4.8 (very good), the broad group cocba test received a score of 4.6 (very good), and the model effectiveness test in enhancing students' soft skills yielded a sigmification value of 0.000 (<0.05) using an independent sample t test. The conclusion is that the histoentrepreneurship model has a positive influence on improving the soft skills of students